New perspectives on Adobe Photoshop CS6 comprehensive - Hosie-Bounar, Jane; Hart, Kelly; Geller, Mitch (Course Technology/Cengage Learning, 2014)
Offers a critical-thinking approach to teaching Web design. This book explains and reinforces design software concepts and skills through the New Perspectives' signature case-based, problem-solving pedagogy